A companion to the Latin language - Clackson, James (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2011)
A Companion to the Latin Language presents a collection of original essays from international scholars that track the development and use of the Latin language from its origins to its modern day usage. Brings together contributions from internationally renowned classicists, linguists and Latin language specialistsOffers, in a single volume, a detailed account of different literary registers of the Latin languageExplores the social and political contexts of LatinIncludes new accounts of the Latin language in light of modern linguistic theorySupplemented with illustrations covering the developme.
Sources -- The language -- Latin through time -- Literary registers of Latin -- Latin in social and political contexts.
Includes bibliographical references and indexes.
Print version record.
Keywords: Latin language -- History; Latin philology; FOREIGN LANGUAGE STUDY -- Latin; Latin language; Latin philology; Latein; Latin -- historia; Klassisk filologi; Electronic books; History